APPLICATION OF COUNSELING SERVICES AT STATE ISLAMIC JUNIOR HIGH SCHOOL (MTSN) IN MEDAN CITY - Henny Syafriana Nasution; Saiful Akhyar Lubis; Lahmudin Lubis (State Islamic University of North Sumatra Indonesia, 2019)
Guidance and counseling is needed in the world of education. As the goal, Education is to develop the character of students, the Mutal Guidance and Counseling is one of the instruments for forming these characters, because Guidance and Counseling has special tips for treating students humanely and well. This study aims to determine the extent of Guidance and Counseling practice conducted at the State Islamic Junior High School (MTsN) in the city of Medan. By using a descriptive qualitative research approach, this research involves a variety of important elements in MTsN in Medan, among others, principals, school counselors, subject teachers and vice principals in student affairs. This study found the results that the Guidance and Counseling Practices conducted at MTsN in Medan city had fulfilled the Standard Operating Procedures for implementing Guidance and Counseling. so that students can be supervised by their character in accordance with what is desired by the educational institution. Thus, the Practice of Guidance and Counseling in MYsn in Medan City can continue to be developed and used as a pilot project to be implemented in Private MTs in Medan and other cities. Keywords: Guidance and Counseling Implementation, State Islamic Junior High School (MTsN) in Medan City,